Adolescence binge alcohol consumption induces hippocampal mitochondrial impairment that persists during the adulthood. (15th May 2019) - Tapia-Rojas, Cheril; Torres, Angie K.; Quintanilla, Rodrigo A.
Abstract: Binge alcohol drinking is a well characterized consumption pattern related with drinking five or more alcoholic beverages during a short period of time followed by a non-drinking period. Several studies showed that this pattern of alcohol intake is becoming very popular among adolescents. However, little is known about the cellular mechanisms involved in ethanol toxicity under these conditions and if these negative changes could be extending to the adulthood. We previously reported that adolescent binge-ethanol consumption impairs brain function acutely. More importantly, we found that animals exposed to this alcohol treatment showed a decrease in the ATP production that remain over time. Therefore, in the present study, we will evaluate the mitochondrial and oxidative alterations that could occur in the adult hippocampus of rats exposed to a unique binge-drinking episode during the adolescence. Our results indicate that adult hippocampus after one adolescent binge-drinking episode presents an increase in the reactive oxygen species production accompanied of mitochondrial dysfunction. Adolescent binge-like ethanol exposure reduced the expression of the mitochondrial respiration complexes, induced mitochondrial depolarization, increased mitochondrial calcium levels, and reduced ATP production in the adult hippocampus. Altogether, our results indicate that adolescence binge alcohol drinking affects the electron transport chain components expression resulting in mitochondrial failure and loss of calcium buffering in the adult hippocampus. Therefore, we reported for first time that adolescent binge-alcohol consumption has severe repercussions on mitochondrial bioenergetics during the adulthood; and that this is not a transitory change until the state of drunkenness disappears as previously believed. Highlights: Adolescent binge-drinking induces ROS production in the adult hippocampus. Binge-ethanol exposure during adolescence reduces the levels of OXPHOS protein in the adulthood. Binge-alcohol exposure in adolescence promotes mitochondrial depolarization in adult hippocampal tissue. Adolescent binge-ethanol exposure results in a loss of mitochondrial calcium regulation 7 weeks after exposure. Adolescent binge-drinking impairs mitochondrial redox, bioenergetics and calcium buffering which persist during the adulthood.